PERSEPSI MASYARAKAT KELURAHAN PASIRAN TERHADAP HUTAN KOTA GUNUNG SARI KECAMATAN SINGKAWANG BARAT KOTA SINGKAWANG - Muhammad, Fadli; Lumangkun, Augustine; Idham, M. (JURNAL HUTAN LESTARI, 2016)
The urban forest of Gunung Sari in Pasiran District is one of the alternatively primary source, for the local people. The purpose of this research is to know the perception of Pasiran people and the that which have relationship toward urbanforest of Gunung Sari. This research was conducted in September 2015.The wish used in this research is survey method descriptively with interview technique.The sampels were collected by purposive sampling andthe numbers of respondents are 90.The research result shows that52respondents (57,78%) of Pasiran people have high perception toword city forest of Gunung Sari, 25respondents(27,28%) are moderate, and13 (14,44%) are low. The high perception respondents toward urban forest of Gunung Sari is because they are aware have realized how of the importance of urban forest for their lives. Key Word :Peopleperception,urban forest